Student Advocacy in Canadian Counselling Psychology Programs: 2018 CCPC Working Group Outcomes - Landine, Jeff; Van Vliet, K. Jessica; Hobbs, Chelsea; Chan Kent, Alysha (Canadian Journal of Counselling and Psychotherapy, 2020)
The second Canadian Counselling Psychology Conference, held in Calgary in October 2018, provided an opportunity for conference attendees to participate in one of seven working groups that met over the course of 2 days. Members of one group were tasked with delving into the topic of student advocacy in Canadian counselling psychology. Student advocacy was defined as students speaking up for themselves about what they need in their various graduate programs and educational experiences across Canada. The resulting discussion identified the following broad areas of need and potential program improvement: (a) practicum process and opportunities, (b) preparation for the “real world,” (c) partnerships between university programs and professional communities, (d) increased student funding, and (e) clarity and consistency in program requirements and professional credentialing. Members of the working group developed detailed recommendations and plans of action for each of these areas. This paper reviews the relevant literature on the above topics and expands upon the group’s recommendations for addressing the needs of counselling psychology students in Canada.